Prevalence of Calodium hepaticum (SYN. Capillaria hepatica) in Rattus norvegicus in the urban area of Rio de Janeiro, Brazil - Simões, Raquel de Oliveira (2014)
Universidade Federal Rural do Rio de Janeiro. Curso de Pós-Graduação em Ciências Veterinárias. Seropédica, RJ, Brasil.